FAKTOR – FAKTOR PENGARUH KINERJA KEUANGAN BANK - Marcellus Anggara Hanafi, Elsa Imelda (Jurnal Paradigma Akuntansi, 2020)
The Purpose of this journal is to investigate factors influencing financial performance of banking companies listed in Indonesia Stock Exchange (IDX). This research done by multiple regression model for 43 listed banking companies for the period of 2015-2017. Findings suggest that capital adequacy dan management efficiency have an impact to financial performance, Asset quality, liquidity management, gross domestic product, dan inflation do not appear to influence financial performance.